Event Sponsorship and Brand Loyalty: Mediating Role of Attitude Toward Sponsored Events and Sponsoring Brand - Toan, Nguyen Dinh (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 2 No 2, 2022)
This research is to investigate the impact of event sponsorship on consumers’ brand loyalty through attitudes toward sponsoring brand and sponsored event. Structural equation modelling (SEM) was conducted to test hypotheses with the survey data of 282 Vietnamese youth who have ever watched and followed the Rap Viet 2020 event. The findings indicated that congruity between event image and sponsoring brand image, self-congruity with sponsoring brand image, and attitude towards sponsored event had a significant positive effect on attitude towards sponsoring brand. Attitude towards sponsoring brand, self-congruity with sponsoring brand image, and self-congruity with event image had a significant positive effect on brand loyalty. Congruity between event image and sponsoring brand image, self-congruity with sponsoring brand image, and self-congruity with event image had a significant positive effect on sponsored event attitude. The congruity between event image and sponsoring brand image, self-congruity with sponsoring brand image influence sponsoring brand loyalty by mediating the effects of event attitude and sponsoring brand attitude. Self-congruity with event image influenced sponsoring brand loyalty by mediating event attitude and sponsoring brand attitude. Based on the research’s empirical analysis, some implications were proposed to help sponsor and sponsee managers on how to improve the effectiveness of sponsorship activities.